S-band Brillouin/erbium fiber laser for DWDM application - Harun, Sulaiman Wadi; Cheng, Xiau San; Ahmad, Harith (World Scientific Publishing, 2006)
A multi-wavelength Brillouin erbium fiber laser (BEFL) which operates in a short wavelength band (S-Band) is demonstrated using a depressed cladding erbium-doped fiber (EDF). Two 80/20 couplers were used in the system for internal feedback of generated stokes signal in order to produce cascaded Brillouin stokes for multi-wavelength operation. It generates an optical wavelength comb with spacing of approximately 0.084m. A stable output laser of up to 7 lines was obtained with a Brillouin pump of 3.5 mW, a 980 nm pump laser of 200 mW and an EDF length of 20 m. The BEFL has the potential to be used in the future dense wavelength division multiplexing (DWDM) communication system.